Innovative Methods in Primary Education - Karshiboyeva Khurinisa Karimovna (European International Journal of Pedagogics, 2025)
This article analyzes the role of innovative methods in primary education, their theoretical foundations and practical application. In order to increase the effectiveness of education in modern society, in addition to traditional educational methods, new approaches are widely used - blended learning, gamification, open discussions and debates, as well as methods such as STEM and STEAM. The article discusses in detail the advantages of these methods, their connection with pedagogical theories and ways to effectively implement them in the classroom. The role of information technologies in modern education is also considered.